2015
DOI: 10.1039/c5mb00326a
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized readout strategy for endogenous histone deacetylase activity

Abstract: Histone deacetylases are important drug targets, which are difficult to characterize due to their poor accessibility. We have developed a miniaturized assay for the multi-site readout of deacetylase activity and profiled the substrate selectivity of HDACs for acetylation sites on histone H4 and tumor suppressor protein p53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…[12] In case of HDAC8, the recombinant enzyme shows astrong preference for p53-K382ac-derived substrates,but the pull-down experiments with the p53 probes do not support amajor role of this HDAC in the deacetylation of K382ac. In order to validate whether the pull-down experiments with the newly established HDAC probes enable proper predictions of deacetylase substrate selectivity,westudied the catalytic properties of selected HDACsincellular lysates.Wehave previously shown that global deacetylase activity in cellular lysates can be monitored with synthetic acetylated peptides by MALDI-TOFM S. [13] We synthesized ap 53-derived peptide substrate with acetylated K382 that was readily deacetylated by endogenous HDACsf rom cell lysates ( Figure S7). An isotope-labeled reference peptide was used to quantify the amount of formed deacetylated product.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[12] In case of HDAC8, the recombinant enzyme shows astrong preference for p53-K382ac-derived substrates,but the pull-down experiments with the p53 probes do not support amajor role of this HDAC in the deacetylation of K382ac. In order to validate whether the pull-down experiments with the newly established HDAC probes enable proper predictions of deacetylase substrate selectivity,westudied the catalytic properties of selected HDACsincellular lysates.Wehave previously shown that global deacetylase activity in cellular lysates can be monitored with synthetic acetylated peptides by MALDI-TOFM S. [13] We synthesized ap 53-derived peptide substrate with acetylated K382 that was readily deacetylated by endogenous HDACsf rom cell lysates ( Figure S7). An isotope-labeled reference peptide was used to quantify the amount of formed deacetylated product.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In order to validate whether the pull‐down experiments with the newly established HDAC probes enable proper predictions of deacetylase substrate selectivity, we studied the catalytic properties of selected HDACs in cellular lysates. We have previously shown that global deacetylase activity in cellular lysates can be monitored with synthetic acetylated peptides by MALDI‐TOF MS . We synthesized a p53‐derived peptide substrate with acetylated K382 that was readily deacetylated by endogenous HDACs from cell lysates (Figure S7).…”
Section: Figurementioning
confidence: 99%
“…Um zu überprüfen, ob die Pulldown‐Versuche mit den neu etablierten HDAC‐Sonden ein korrektes Vorhersagen der Substratselektivität der Deacetylase ermöglichen, untersuchten wir die katalytischen Eigenschaften von ausgewählten HDACs in Zelllysaten. Wie zuvor gezeigt, lässt sich die globale Deacetylase‐Aktivität in Zelllysaten mit synthetischen acetylierten Peptiden mittels MALDI‐TOF‐MS quantitativ bestimmen . Ein p53‐Peptid‐Substrat mit acetyliertem K382 wurde im Folgenden durch endogene HDACs aus Zelllysaten deacetyliert und die Produktbildung unter Zuhilfenahme eines isotopenmarkierten Referenzpeptids quantitativ untersucht (Abbildung S7).…”
Section: Figureunclassified
“…HDAC‐catalysis requires metal ions for water activation in order to cleave the N ε‐amide bond of acetyllysine substrates. Although there is evidence that recombinant HDAC8 can utilize Co 2+ and Fe 2+ , in most cases Zn 2+ is considered as the catalytic metal ion of HDACs . Based on this, hydroxamic acid compounds that chelate the catalytic Zn 2+ ion are among the most potent HDAC inhibitors.…”
Section: Introductionmentioning
confidence: 99%